Pengaruh Teknologi pada Kecerdasan Gen Z Dilihat dari Perspektif Islam - Ari Fajar Isbakhi; Widiyatmoko Widiyatmoko; Wahyu Isnaeni (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
In essence, technology has become an inseparable part of Gen Z's life. However, inappropriate use of technology can impact their development. The technology that exists today, has a great influence on the progress of a nation and for that the role of parents and educators must be able to encourage as well as provide control and supervision to children so that they are not addicted to technology. because with technology can expand knowledge through the internet and digital devices, increase creativity to be creative in developing skills and can facilitate learning. However, current technology can also have negative impacts such as children becoming dependent and spending time in front of the screen, social interactions, even children are more interested in front of the screen than playing in the surrounding environment. The purpose of this study is to analyze the influence of technology on Gen Z from an Islamic perspective and how to implement it. The research method used is a qualitative method with a library research approach. The results of this study indicate that the influence of technology on Gen Z is very large, this is because technological advances require everyone to be able to operate technology. However, it must be balanced with the role of Islam, namely character education. Character education has a higher meaning than moral education, therefore character education not only teaches right and wrong, but also instills habits (habituation) about what is good so that Gen Z understands, is able to feel, and wants to do what is good. In the Islamic perspective, character is called morality. The components of moral or personality education include: knowledge, attitudes, and behavior and are identical to the teachings of Islam itself which are sourced from the Quran and Hadith.